Critical realism: a philosophical framework for the study of gender and mental health - Bergin, Michael (Nursing philosophy, 2008)
This paper explores gender and mental health with particular reference to the emerging philosophical field of critical realism. This philosophy suggests a shared ontology and epistemology for the natural and social sciences. Until recently, most of the debate surrounding gender and mental health has been guided either implicitly or explicitly within a positivist or constructivist philosophy. With this in mind, key areas of critical realism are explored in relation to gender and mental health, and contrasted with the positions of positivism and constructivism. It is argued that critical realism offers an alternative philosophical framework for the exploration of gender issues within mental health care.